PENGARUH BUDAYA ORGANISASI, LOCUS OF CONTROL DAN STRES KERJA TERHADAP KEPUASAN KERJA PADA SUPER DAZZEL CABANG YOGYAKARTA - Wuri Pawestri; Muhammad Robi Nurwahyudi; Zaenab Alboneh (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
Job satisfaction is a condition where employees feel satisfied with their work. People who express high satisfaction in their work tend to be more productive. The purpose of this study was to analyze the influence of organizational culture, locus of control and job stress on job satisfaction. This research was conducted on 40 respondents at Super Dazzel Yogyakarta Branch.The method used in this research is quantitative with classical assumption test and multiple linear regression analysis, namely between organizational culture variables (X1), locus of control (X2), and job stress (X3) on job satisfaction (Y), F test ( simultaneous), t-test (partial) in order to determine how much influence locus of control organizational culture and job stress have on employee job satisfaction at Super Dazzel Yogyakrata Branch.Based on the results in this study, in general, organizational culture, locus of control and job stress have a significant effect on job satisfaction.